Book Reviews (Blackfriars, 1926)
Book Reviews in this Article Rome, Past and Present. By William Gaunt, B.A. Special Spring Number of The Studio, 1926. Saint Francis. An Historical Drama. By Fr. Cuthbert, O.S.F.C. Virginibus Christi. Conferences for Nuns. By Mother St. Paul. The Sacrifice of the New Law. By J. Brodie Brosnan. How to Pray Always. Principles and Practices for Attaining to Union with God. By Raoul Plus, S.J. Translated by Irene Hernaman.